2016
DOI: 10.1016/j.neucom.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Orthogonal Forward Regression Algorithms for the Identification of Non-Linear Dynamic Systems

Abstract: A new Ultra Least Squares (ULS) criterion is introduced for system identification. Unlike the standard least squares criterion which is based on the Euclidean norm of the residuals, the new ULS criterion is derived from the Sobolev space norm. The new criterion measures not only the discrepancy between the observed signals and the model prediction but also the discrepancy between the associated weak derivatives of the observed and the model signals. The new ULS criterion possesses a clear physical interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…From the search perspective, the OFR is a sequential greedy approach where the term with the highest performance metric, referred to as Error-Reduction-Ratio (ERR), is included in each step and it has proven to be very effective in various applications [3,11]. However, it has been shown that under certain conditions the OFR may yield sub-optimal term subsets [12][13][14][15][16]. The reason for such suboptimal performance is often attributed to the performance metric, ERR.…”
Section: Introductionmentioning
confidence: 99%
“…From the search perspective, the OFR is a sequential greedy approach where the term with the highest performance metric, referred to as Error-Reduction-Ratio (ERR), is included in each step and it has proven to be very effective in various applications [3,11]. However, it has been shown that under certain conditions the OFR may yield sub-optimal term subsets [12][13][14][15][16]. The reason for such suboptimal performance is often attributed to the performance metric, ERR.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, some authors have adapted the original OFR algorithm to optimize directly the MPO in order to obtain a better long‐term prediction. However, these modified versions tend to be computationally expensive during the feature selection step, and a much better alternative is to use the iterative or ultraorthogonalization approach [ Guo et al , , ].…”
Section: Nonlinear System Identificationmentioning
confidence: 99%
“…However, because the NARX model (1) depends on past outputs, a more reliable way to check the validity of the model is through the model-predicted output (MPO), which uses past predicted outputs to estimate future ones and to provide details about the stability and predictability range of the model, In the literature, some authors have adapted the original OFR algorithm to optimize directly the MPO in order to obtain a better long-term prediction. However, these modified versions tend to be computationally expensive during the feature selection step, and a much better alternative is to use the iterative or ultraorthogonalization approach [Guo et al, 2015a[Guo et al, , 2015b].…”
Section: Appropriate Model Term Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, this notion of the original OFR approach has been refined to further improve the search performance. These include OFR approaches with either new term evaluation criteria [17][18][19][20] or improved search strategies [21][22][23][24][25]. A detailed treatment on this subject can be found in the recent investigation by the authors [25].…”
mentioning
confidence: 99%